Liver disease in transfusion dependent thalassaemia major. Issue 5 (1st May 2002) - Li, C K; Chik, K W; Lam, C W K; To, K F; Yu, S C H; Lee, V; Shing, M M K; Cheung, A Y K; Yuen, P M P
Abstract : Aims: To study the prevalence and severity of liver diseases of transfusion dependent thalassaemia major patients, and correlate the histological and biochemical changes of iron overload in liver with the peripheral blood markers. Method: Liver biopsy was performed to assess the histological changes and liver iron content (LIC). Results: One hundred patients were evaluated (median age 11.7 years, range 1.5–27). A total of 81 liver biopsies were performed in 73 patients; 43 samples were analysed for LIC. Grade 3–4 haemosiderosis and hepatic fibrosis was found in 44% and 30% of patients respectively; both were significantly associated with higher serum ferritin, liver enzymes, and LIC. Very high LIC (>15 mg/g dry weight) was present in 16.3% of patients. Conclusion: Severe haemosiderosis and hepatic fibrosis were common in patients with thalassaemia major despite the use of chelation therapy. Liver biopsy provided information on fibrosis and LIC which could not be accurately predicted from peripheral blood markers.